Effect of dripper discharge on spatio-temporal movement of water in soil under drip irrigation - KUMAR, MUKESH; RAJPUT, T.B. S.; PATEL, NEELAM (Journal of Soil and Water Conservation, 2021)
Drip irrigation is an advanced and efficient method irrigation to use water efficiently. Water distribution in soil is one of the most important parameters to design efficient drip irrigation system. Soil texture, structure, initial soil moisture, and dripper discharge are the important factors on which extent of wetting front in soil mainly depends. An actual field research was conducted to investigate the effect of dripper discharge at different system operating pressures on spatio-temporal soil moisture movement. The value of moisture contents varied significantly (P